AGMEMOD MODEL – STRUCTURE AND APPLICATION FOR ANALYSIS AND SIMULATION OF POLISH AGRICULTURAL SECTOR - Hamulczuk, Mariusz; Hertel, Katarzyna (Metody Ilościowe w Badaniach Ekonomicznych, 2009)
The aim of this paper was to present the AGMEMOD1 model as anexample of partial equilibrium model applied in the field of agricultural economics and its capacity to evaluate changes in the Common Agricultural Policy (CAP). The AGMEMOD model is an econometric, dynamic, multiproduct, partial-equilibrium modelling system constructed within the 5th and6th EU Framework Project. As an example of application of the model aquantitative assessment of the impact of the milk quotas abolition on the Polish dairy sector was displayed.